Tanzania Economic Update, January 2019 : The Power of Investing in Girls - World Bank Group (World Bank, Washington, DC, 2019)
Economic performance in 2018 has been mixed. The data that are available suggest some areas of softening in the economy.1 Foreign direct investment declined to 2 percent of GDP in 2017, down from about 5 percent in 2014. The current account deficit has increased to 3.8 percent of GDP in the year ending September 2018, from 2.2 in the preceding 12 months. Recent Bank of Tanzania data confirm lower cashew exports and 2017 decline in non-traditional exports has continued into 2018, which raises concerns on prospects for longer term growth. The Tanzania Revenue Authority is reporting that many large tax payers are unable to meet their tax obligations on time. Nonperforming loans have declined recently to 9.7 percent in September 2018 from 12.5 percent in September 2017, but remain almost double the 5 percent statutory threshold. Banks have limited lending to businesses and interest rates are high (18 percent for one-year loans in August 2018), though some banks have lowered benchmark lending rates. On a positive note, credit to the private sector has been edging up, reaching 4.9 percent in the 12 months ending September 2018. The fiscal deficit is still low, not counting payment arrears and delayed refunds of value-added tax. The 2017/18 budget deficit after grants of 1.3 percent of GDP suggests effective spending management but does not factor in payment arrears, with an estimated stock of over 3 percent of GDP. Government is paying down roughly TZS 1 trillion of verified arrears per fiscal year. The low deficit is the result of controlled recurrent expenditures and under execution of the development budget by more than 40 percent. Contributing factors include shortfalls in domestic revenue and external financing for large projects. Public debt is currently sustainable, but there is need for the Government to consider cost-effective financing options and manage associated risks to support public investments. The 2018/19 budget targets public investment to consume 45 percent of total spending, equivalent to 9.1 percent of GDP compared to 5.5 a year prior.